The Effects of Chronic Naltrexone on Reinstatement of Opioid-Induced Drug-Seeking Behavior and Antinociception - Withey, Sarah L; Bergman, Jack; Paronis, Carol A (The Journal of pharmacology and experimental therapeutics, 2024)
Opioid addiction is a chronic relapsing disorder in which drug-seeking behavior during abstinence can be provoked by exposure to a -opioid receptor (MOR) agonist or opioid-associated cues. Opioid self-administration behavior in laboratory subjects can be reinstated by priming with MOR agonists or agonist-related stimuli, providing a procedure suitable for relapse-related studies. The opioid antagonist naltrexone has been forwarded as a medication that can forestall relapse and, in an extended-release formulation, has demonstrated some treatment success. However, chronic naltrexone treatment has not been extensively investigated in nonhuman subjects and aspects of its pharmacology remain uncertain. For example, the relative effectiveness of naltrexone in reducing the priming strength of opioid agonists differing in efficacy is not well understood. Here, using intravenous self-administration and warm-water tail withdrawal procedures, we investigated changes in the direct reinforcing effects of oxycodone and in the priming strength and antinociceptive effects of opioid agonists in squirrel monkeys ( = 4) during chronic treatment with naltrexone (0.2 mg/kg/d). Results show that naltrexone produced: 1) a 10-fold rightward shift in the dose-response function for the reinforcing effects of oxycodone, and 2) in reinstatement and antinociception experiments, comparable rightward shifts in the dose-response functions for higher-efficacy MOR agonists (methadone, heroin, and oxycodone) but rightward and downward shifts in the dose-response functions for lower-efficacy MOR agonists (buprenorphine, nalbuphine, and butorphanol). These results suggest that, although chronic naltrexone should be effective in forestalling relapse following exposure to lower- and higher-efficacy agonists, the inability of lower-efficacy agonists to surmount naltrexone antagonism may complicate the prescription of opioids for pain. SIGNIFICANCE STATEMENT: Although naltrexone is commonly used in the treatment of opioid use disorder, its ability to reduce the priming strength of opioid agonists has not been extensively investigated. This study shows that chronic naltrexone treatment induces rightward shifts in the reinstatement and antinociceptive properties of higher efficacy opioid agonists, but rightward and downward shifts for lower efficacy opioid agonists, suggesting lower efficacy agonists may not be able to surmount naltrexone-induced antagonism of these two effects, and perhaps naltrexone offers greater protection against lower efficacy agonists.